Geological characteristics and main enrichment controlling factors of coalbed methane in Nanchuan area, southeastern Sichuan Basin - Xipeng HE; Kaiming WANG; Wei LUO; Yuqiao GAO; Nana LIU; Tao GUO; Yatong ZHOU; Didi WU (Shiyou shiyan dizhi)
A significant strategic breakthrough has been achieved in the exploration of deep coalbed methane (CBM) in the Upper Permian Longtan Formation in the Nanchuan area, southeastern Sichuan Basin, showing promising exploration potential for CBM in this area. To identify the main geological factors controlling its enrichment, this study used data from drilling, cores, well logging, and experimental analyses to investigate the geological characteristics and main controlling factors for CBM enrichment, focusing on coal seam distribution, coal quality, physical properties, gas content, and fracturability characteristics of the Longtan Formation. The results show that: (1) The main coal seams of the Longtan Formation exhibit stable distribution (thickness of 2.8 to 5.7 m), good coal body structure (mainly primary structural coal), high vitrinite content (average content of 79.7%), high degree of thermal evolution (average Ro of 1.9%), and low ash yield rate (average of 14.3 %). These characteristics provide the basic conditions for the formation of CBM reservoirs. (2) The coal reservoir has a pore-fracture structure, with micropores accounting for 78% of the total pore volume and contributing 99.6% of the total specific surface area, which is favorable for CBM adsorption and post-fracturing seepage. (3) The total gas content of the coal seam is 14.0 to 46.7 m3/t, with free gas accounting for 39% to 44%. It is characterized by "high gas content, abundant free gas, and oversaturation", and its gas content increases with burial depth. (4) The in-situ stress in the study area is moderate (35 to 60 MPa), with a small two-way horizontal stress difference coefficient (< 0.1) and good roof and floor plates, forming effective stress shielding favorable for fracturing transformation. (5) The main controlling factors for CBM methane enrichment in the Nanchuan area include the sedimentary environment, which determines coal-bearing formations; the degree of coal evolution, which determines the intensity of hydrocarbon generation; and the preservation conditions, which govern CBM enrichment.